Physics and Dynamics Characteristics and Energy Analysis of Freeze-Thaw Limestone - Qi Ping; Hongjian Sun; Chuanliang Zhang; Xin Zhou (Advances in Civil Engineering)
In order to study the physical and dynamic properties of rock after damage, an open-type saturated water freeze-thaw test at ±20°C was carried out on the limestone specimen, the size, quality, and longitudinal wave velocity with measured after freeze-thaw cycles for 0, 10, 20, 30, 40, 50, 60, 70, 80, 90, and 100 times, and the SHPB test device was used to carry out the impact compression test with eight kinds of loading rate. This text analyzes the damage evolution characteristics on the physical properties of limestone of cycle times of freeze-thaw and discusses the dynamic compression mechanical characteristics and energy dissipation law of limestone specimens after freeze-thaw cycles. The test results show that the mass and longitudinal wave velocity of the specimen decreased and the volume and density increased. The damage factors have the quadratic function positive correlation with the cycle time of freeze-thaw. Moreover, the dynamic compression stress-strain curves of the specimens under different loading rates are similar in shape, and the curve shows an upward trend with increasing loading speed. In addition, with the loading rate increasing, the dynamic compressive strength and dynamic elastic modulus of the specimen increased and the dynamic strain decreased. In the SHPB test, the reflected energy, transmitted energy, and absorbed energy all increased linearly with incident energy. The dynamic compressive strength and absorbed energy increase as a power function, and the strain rate and absorbed energy increase as a quadratic function.